Developmental Change in Motor Competence: A Latent Growth Curve Analysis - Coppens, Eline; Bardid, Farid; Deconinck, Frederik J. A.; Haerens, Leen; Stodden, David; D’Hondt, Eva; Lenoir, Matthieu (Frontiers in Physiology, 2019)
Background: The development of childhood motor competence demonstrates a high degree of inter-individual variation. Some children’s competence levels increase whilst others’ competence levels remain unchanged or even decrease over time. However, few studies have examined this developmental change in motor competence across childhood and little is known on the influencing factors). Aim: Using latent growth curve modeling (LGCM), the present longitudinal study aimed to investigate children’s change in motor competence across a two-year timespan and to examine the potential influence of baseline weight status and physical fitness on their trajectory of change in motor competence. Method: 558 children (52.5% boys) aged between 6 and 9 years participated in this study. Motor assessments took place three times across a two-year timespan. Baseline measurements included weight status, motor competence (i.e., Körperkoördinationstest für Kinder; KTK) and physical fitness (i.e., sit and reach, standing long jump and the 20m shuttle run test). LGCM was conducted to examine change in motor competence over time, based on the raw scores of the four KTK subtests. Results: The analyses showed a positive linear change in motor competence across two years (=28.48, p<.001) with significant variability in children’s individual trajectories (p<.001). Girls made less progress than boys (=-2.12, p=.01). Children who were older at baseline demonstrated less change in motor competence (=-0.33, p<.001). Weight status at baseline was negatively associated with change in motor competence over time (=-1.418, p=.002). None of the physical fitness components, measured at baseline, were significantly associated with change in motor competence over time. Conclusions and Implications: This two-year longitudinal follow-up study reveals that weight status significantly influences children’s motor competence trajectories whilst physical fitness demonstrated no significant influence on motor competence trajectories. Future studies should further explore children’s differential individual trajectories over time and potential factors influencing that change.